Peningkatan Keterampilan Anggota WKRI Cabang Kristus Raja Semesta Alam Mopah Lama Merauke dalam Pengolahan Limbah Batang Pisang menjadi Gedebog Crispy - Yosefina Mangera; Rosmayasinta Makasau (Yayasan Literasi Sains Indonesia, 2024)
Bananas are one type of plant that many people plant in their yards or gardens. Banana trees consist of parts that have very high utility value, one of which is the banana stem. Banana stems have high nutritional value and can be processed into snacks for the family. Mothers who are members of the WKRI organization, KRSA Mopah Lama Merauke Branch, are invited to become skilled in utilizing natural ingredients available around them to make nutritious food for the family and can increase the family's economic income. Training on processing banana stem waste into crispy gedebog is one form of activity in order to improve the skills of WKRI women in processing natural waste which is very beneficial for the family. The method used in this activity is socialization about the benefits of banana stem waste and its nutritional value and direct training or practice in making crispy gedebog. The results of this training show that there is a transfer of knowledge to WKRI mothers. This was shown by the enthusiasm of the mothers in participating in the training activities through various questions asked of the presenters and their involvement in joint practice. This training adds new skills for WKRI women in managing banana stem waste into nutritious food for the family and can be used as innovation in entrepreneurship.